Assessment of employee’s knowledge potential in transport sector - Morkvėnas, Renatas; Bivainis, Juozas; Jaržemskis, Andrius (Transport, 2008)
Although plenty of scientists have researched the theoretical and practical problems of assessing knowledge potential for a few decades, the unified and single methodology of assessment has not been accepted. Discussions on the factors having the strongest impact on the knowledge potential of employees have been processed. The method stated in this article is adopted to transport sector. An evaluation of specifications for the factors making a real impact helped with building a model including such factors as educational level, occupational experience, occupation level, dutifulness, decision making and responsibility level, self‐support at work, work culture, difficulty level at work, motivation, employee’s influence on achieving organization’s aim and the level of using technology at work. The specifications of the above introduced factors have been prepared. Practical acceptance of the model has been researched by an experiment conducted in a transport company. First published online: 27 Oct 2010